Allocation of farm output and farmer-agribusiness linkages: cyclical decisions and welfare effects - Aseete, Paul (Kansas State University, 2021)
Agricultural commercialization has been a major development policy in Uganda as in most of Sub-Saharan Africa. The quest is to use agriculture as an engine of development to ensure high income, food security, and industrialization. While effort has been placed in implementing programs targeted towards commercialization, levels of subsistence farming are still high. This dissertation contributes three essays aimed at understanding: (1) output allocation on smallholder farms and determinants of allocation choice, (2) production and income thresholds that may foster increased market participation by smallholder farmers, and (3) the economic benefits created by Ag-Public Private Partnerships (Ag-PPP) to small holder farmers. The first essay (chapter 2) models the farm output allocation process, among Ugandan farmers, to show how farmers distribute production, and documents factors that influence the choice of an allocation strategy. It thus evaluates both participation and the level of allocations. The study analyzes the ex-post decision when output is known with certainty and argues that households maximize utility at this stage; ex-ante decisions become inconsequential at this point. The study finds that levels of self-provisioning are high, approximately 66% of produced output, while commercialization stands at 27%. Furthermore, findings show that crop diversification increases the share of output allocated to home consumption and reduces that for marketing and storage. Non/off-farm income eases the burden of producing for the market – farmers with higher off-farm incomes tended to produce and allocate more for home use. Also, farmers with high output tended to allocate more to the market. We found that household food sufficiency reduced the share allocated to the market and was associated with higher shares allocated to storage. Adopting a policy prescribed enterprise increased shares given to the market and storage and decreased the share for home use. The significance and size of effects on choice of allocation strategy varied by farm size and shock exposure. The second essay (Chapter 3) analyzes the conditions that are necessary to motivate farmers to supply larger output levels to the market. The study investigates this problem by assessing if there exist production and nonfarm income thresholds at which farms can release more output for the market while staying food sufficient. Exploiting temporal and spatial variations in Household Food Sufficiency (HFS) and output allocation in Uganda, findings show income and production thresholds much higher than earned annual average non-farm incomes and farm production. These thresholds lead to varied effects of marketing on HFS. Both farm and nonfarm income are positively associated with HFS, and thus market participation, but the farm income effect is dominant. This suggests that implementing farm-based interventions may provide superior results than nonfarm interventions in securing food security and indirectly market participation in developing countries. Findings further show that the effects of policy outcomes may be incongruous with farmer needs and production circumstances if detailed and in-depth procedures are not considered in policy formulation, implementation, and analysis. In the third essay (Chapter 4), the study estimates the effects of an Ag-PPP that sought to create a sustainable Business-to-Business linkage by offering multiple transfers and guarantees to farmers. Here, the economic benefits to farmers, created by the PPP to common bean producers in Uganda is evaluated. Ag-PPPs play critical role in agrarian societies where agriculture is the predominant sector in creating employment, generating GDP, and securing food supply. Findings show that by leveraging the potential to create synergies among actors, the PPP created positive outcomes for farmers and stimulated increased production from targeted interventions. The study documents evidence of a significant increase in sales and sales revenue due to increases in bean production. For example, PPP farmers were likely to report 209 Kg/hectare higher yield compared to non-PPP farmers. Also, PPP farmers were more likely to report positive quantities of production to allocated to the market. Public private partnerships have checks and balances which ensure that benefits are allocated fairly among actors. Thus, the occurrence of scenarios that could marginalize and impoverish the weakest actors, often farmers, is tremendously curtailed.
Keywords: Allocation of farm output; Farmer-agribusiness linkages; Small holder farmers; Uganda; Food security and food policy; Developing countries